One-Year Follow-Up of Corneal Biomechanical Changes After Accelerated Transepithelial Corneal Cross-Linking in Pediatric Patients With Progressive Keratoconus - Jian, Weijun; Tian, Mi; Zhang, Xiaoyu; Sun, Ling; Shen, Yang; Li, Meiyan; Zhou, Xingtao (Frontiers in Medicine, 2021)
Aims: This study aimed to investigate the corneal biomechanical changes and topographic outcomes of accelerated transepithelial corneal cross-linking (ATE-CXL) in pediatric progressive keratoconus. Methods: In this prospective longitudinal study, 31 eyes of 28 pediatric patients with keratoconus (21 boys and 7 girls; mean age, 14.35 ± 2.68 years) undergoing ATE-CXL (epithelium-on procedure with 45 mW/cm2 for 320 s) were included. Corvis ST was used to measure dynamic corneal response parameters at baseline and at 12 months after ATE-CXL. Corneal keratometry and corneal thickness were measured using Pentacam preoperatively and 1, 6, and 12 months postoperatively. Results: No serious complications occurred during or after ATE-CXL. The maximum keratometry values were 60.10 ± 7.51 D preoperatively and 61.42 ± 8.92, 61.17 ± 7.96, and 60.02 ± 7.58 D at 1, 6, and 12 months after ATE-CXL (P > 0.05), respectively. Corneal thickness remained stable during the 12-month follow-up (P > 0.05). At postoperative 12 months, first applanation time (P < 0.001), first applanation length (P = 0.004), second applanation velocity (P = 0.014), highest concavity time (P = 0.022), and radius of curvature at highest concavity (P = 0.031) increased significantly. The value of stiffness parameter at first applanation was significantly increased from 57.70 ± 27.57 preoperatively to 63.36 ± 27.09 at 12 months after ATE-CXL (P = 0.018). Conclusions: ATE-CXL is safe and effective in stabilizing the progression of pediatric keratoconus. Changes in corneal biomechanical response consistent with stiffening following ATE-CXL were observed in pediatric patients with keratoconus.